Hepatocellular carcinoma surveillance with ultrasound—cost-effectiveness, high-risk populations, uptake - Ronot, Maxime (Br J Radiol, 2018)
Hepatocellular carcinoma (HCC) is the most frequent primary liver cancer and the second cause of cancer-related deaths worldwide. In most cases, it is diagnosed in patients with identified risk factors, mainly cirrhosis from all causes. These patients are candidates for a surveillance program that, depending on guidelines, involves regular liver ultrasound alone or combined with serum markers. These programs have been shown to improve the oncological outcome by detecting earlier stage tumors and providing patients with potentially curative treatment and improved survival. Yet, the level of evidence supporting these guidelines remains limited. This review article presents an overview of the evidence supporting surveillance programs for hepatocellular carcinoma, in particular the efficacy, cost-effectiveness, and consequences of this approach for patient survival. Western and Eastern guideline recommendations are described and discussed.